KELAYAKAN DASAR PENERAPAN HACCP DI KAPAL FRESH TUNA LONGLINE - Tri Wiji Nurani; Budhi Hascaryo Iskandar; Gina Almirani Wahyudi (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2011)
Many numbers of rejected tuna product of Indonesia in export market, request fish handling which can qual-ity assurance and security of the product. Fish handling on board is one of the production chain which playing a port of important to quality of tuna product. HACCP quality management system have been obliged to be applied in fish processing unit, while in fishing vessel the traceability. Appling SSOP and GMP/GHP represent a basic requirement (pre requisite) as measuring rod of the readiness of applying HACCP. The purpose of this study was to determine the feasibility of the basic requirements of HACCP implementation in the tuna longline vessels. Research done in the fishing port of Palabuhanratu and Nizam Zachman Jakarta. Assessment conducted to basic requirement of vesselfeasibility, include the location and environment, design andconstruction of ships and facilities, equipment and supplies,operational management, hygiene and health of workers, to thequality management system. Result of the research indicatedthat value Yi around 1,5